PECULIARITIES OF TEACHING MEDICAL TERMINOLOGIES (Academicia Globe: Inderscience Research, 2023)
Language and medicine are two of the most important aspects in the life of mankind. And the language in medicine plays a decisive role in the health of all mankind. A huge responsibility lies with the medical translator when translating certain terms. But no less great responsibility lies with the teacher of a medical translator. Teaching, on its own, is not an easy profession, with the amount of responsibility that cannot be overestimated. Doubly complicating the task of the teacher of the future translator is the huge number of lives saved. If the doctor is the messenger of God on earth, then their interpreters are angels. In this article, I would like to touch on a very non-obvious, but necessary topic - the features of teaching medical terms.